Polymetallic Complexes : Part XXXVI — Z - Donor Bis-Bidentate Chelating Azodye Complexes of Co(II), Ni(II), Cu(II), Zn(II), Cd(II) and Hg(II) - B. Mahapatra, Bipin; Behera, A.K.; K. Bhoi, Promod (Asian Journal of Chemistry, 2010)
4,4´-Bis[5-(8´-hydroxyquinolyl)-azo] benzene and bis[4-(8´-hydroxy-quinolyl-5´)-azo-3-methylphenyl] methane act as bis-bidentate donor chelating ligands and form polymeric complexes with divalent metal ions. The characterisation of the complexes has been made basing upon elemental analysis, conductivity measurements, magnetic moments and spectral (electronic, IR, and ESR) studies. The antibacterial activities of the ligands and a few represnetative complexes have been determined.